Energy-environment-economic study and optimization: An advanced heat recovery method for improving gas turbine cycle efficiency - Chaoxin Ji; Azher M. Abed; Xiao Zhou; Guoliang Lei; Li He; T.H. AlAbdulaal; Barno Abdullaeva; Mohammad Sediq Safi (Case Studies in Thermal Engineering)
This study introduces an innovative system for combined cycle power plants that significantly enhances efficiency and sustainability through advanced heat recovery techniques. By integrating various cycles and units, including the Brayton, Rankine, and Kalina cycles, along with a thermoelectric generator, proton exchange membrane electrolysis hydrogen production unit, and RO desalination unit, the proposed system optimizes performance across multiple dimensions. Multi-objective optimization, employing a genetic algorithm, ensures optimal system performance in terms of energy, exergy, economics, and environmental impact. The novelty of this research lies in its comprehensive approach to combining power generation with water desalination and hydrogen production, thereby addressing multiple energy and environmental challenges simultaneously. The thermodynamic analysis confirms the system's capability to deliver 1.45 MW of electrical power and produce 3.24 kg/h of hydrogen, with a unit cost of production (UCOP) of 10.24 cents/kWh. Key findings highlight the significant impact of gas turbine inlet temperature on system cost and efficiency, and the trade-offs involved in optimizing pressure ratios for peak performance. The optimized system demonstrates an exergy efficiency of 37. 6 % at a cost rate of 57. 2 $/h. The integrated approach not only increases power generation capacity but also enables the production of hydrogen fuel and fresh water, showcasing technological advancements with significant practical applications. The potential prospects of this research include its application in various industrial sectors, contributing to sustainable energy solutions and environmental conservation.